2016
DOI: 10.1149/2.0961608jes
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Electroactive Polymer Gel Film upon Lithiation and Delithiation of PbSe

Abstract: Because lead telluride (PbTe) was found to rapidly and reversibly lithiate to form Li + -conductive Li 2 Te and a series of Li-Pb alloys, we explored the reversibility and rate of lithiation of PbSe. As expected, PbSe was also reversibly lithiated to Li 2 Se and Li-Pb alloys, but the electrode was less stable and could not be cycled as rapidly. When the electrode was cycled at a slow rate, an electroactive polymer gel film derived of the 1 M LiPF 6 in 1:1 fluoroethylene carbonate/diethyl carbonate (w/w) electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Again, this trend was reversed upon full charge . The formation and decomposition of the surface layer can be also confirmed by monitoring electrochemical impedance spectroscopy (EIS) because the diameter of the measured semicircle is commonly ascribed to the resistance from the electrode–electrolyte interface. ,, The diameter increases during lithiation and decreases during delithiation, as seen in Figure k,l). Other analysis techniques such as thermogravimetry and mass spectrometry (TG-MS), time-of-flight secondary ion mass spectrometry (SIMS), ,, Fourier transform infrared spectroscopy (FTIR), and infrared reflection absorption spectroscopy (IRRAS) have also been used to demonstrate the formation and decomposition of electrolyte-derived surface layer.…”
Section: Phenomena Proposed To Give Rise To Abnormal Reversible Capacitymentioning
confidence: 99%
“…Again, this trend was reversed upon full charge . The formation and decomposition of the surface layer can be also confirmed by monitoring electrochemical impedance spectroscopy (EIS) because the diameter of the measured semicircle is commonly ascribed to the resistance from the electrode–electrolyte interface. ,, The diameter increases during lithiation and decreases during delithiation, as seen in Figure k,l). Other analysis techniques such as thermogravimetry and mass spectrometry (TG-MS), time-of-flight secondary ion mass spectrometry (SIMS), ,, Fourier transform infrared spectroscopy (FTIR), and infrared reflection absorption spectroscopy (IRRAS) have also been used to demonstrate the formation and decomposition of electrolyte-derived surface layer.…”
Section: Phenomena Proposed To Give Rise To Abnormal Reversible Capacitymentioning
confidence: 99%
“…It is widely accepted that the irreversible electrochemical reaction of an electrolyte leads to form SEI on the surface of carbonaceous anode material upon the first discharge (Li insertion) process. Once SEI is properly formed with the help of well-adjusted electrolyte composition, the formed SEI layer prevents not only further decomposition of the electrolyte but also mechanical deformation of carbonaceous anode material mainly caused by solvent co-intercalation into graphene layer, thereby stabilizing the electrochemical reaction of carbonaceous anode materials with Li ion. This implies that SEI acts as a passivation film to ensure reversible electrochemical Li storage and removal reaction during cycling. , On the other hand, recent reports revealed that the reversible formation and decomposition of SEI layer are able to occur on the surface of some transition metal oxide anode materials even after the first cycle. Laruelle et al first reported that reversible formation and decomposition of the gel-like polymer are caused by the electrochemical reaction of an electrolyte at the surface of electrode materials, which is contrary to the phenomena observed at carbonaceous anode materials. They stated that extra capacity beyond theoretical capacity of CoO based on the conversion reaction with lithium comes from this reversible electrochemical reaction of the electrolyte during cycling .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10 years, various techniques have been used to help alleviate this capacity loss, such as using nanostructures to reduce particle strain, group 16 chalcogenide additives that act to buffer volume expansion, and carbon coating to passivate particle surfaces, some of which have been applied to lead based anodes. [7][8][9][10][11][12][13][14] The usage of different group 16 chalcogenides to stabilize the cycling stability of lead has been demonstrated by Wood and coworkers. 7,10,11 Within this group (O, S, Se, Te), there is a general improvement in performance with increased atomic number, due to greater atomic radii and polarizability, leading to improved electrical and Li + conductivity.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] The usage of different group 16 chalcogenides to stabilize the cycling stability of lead has been demonstrated by Wood and coworkers. 7,10,11 Within this group (O, S, Se, Te), there is a general improvement in performance with increased atomic number, due to greater atomic radii and polarizability, leading to improved electrical and Li + conductivity. However, Se and Te are less abundant than S by 4 and 5 orders of magnitude, respectively, making them much more expensive, and less practical for potential commercial use.…”
mentioning
confidence: 99%